2015
DOI: 10.5152/tpa.2014.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth in very low birth weight preterm babies

Abstract: Aim: The aim of this study was to evaluate physical growth of very low birth weight (VLBW) preterm babies at a mean age of three years and to investigate the factors which affected growth. Material and Methods:The factors including maternal problems, prenatal problems, early neonatal problems, nutrition, familial socioeconomical status and presence of chronic disease which affected catch-up growth in terms of height and weight in VLBW infants followed up in the neonatal intensive care unit (NICU) of our hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Catch-up growth happened more quickly when infants were PF-fed whereas BF infants increased in weight and length/height over a longer period of time; this indicates a possible difference in growth potential influenced by feeding. Other studies have found that partially BF preterm-born children up to 24 months of age facilitated catch-up growth similar to that of BF term-born infants [17]. This indicates that breast milk possibly contains nutrients that promote long-term growth also in preterm-born infants.…”
Section: Discussionmentioning
confidence: 63%
“…Catch-up growth happened more quickly when infants were PF-fed whereas BF infants increased in weight and length/height over a longer period of time; this indicates a possible difference in growth potential influenced by feeding. Other studies have found that partially BF preterm-born children up to 24 months of age facilitated catch-up growth similar to that of BF term-born infants [17]. This indicates that breast milk possibly contains nutrients that promote long-term growth also in preterm-born infants.…”
Section: Discussionmentioning
confidence: 63%
“…In a longitudinal long-term study, Tenovuo et al (12) reported that SGA premature infants also caught up on growth as AGA infants at two years of age. Yeşinel et al (13) found that gestational age, AGA, SGA, and gender did not cause a significant difference in VLBW premature infants in terms of reaching the target height. Likewise, in the present study, no difference was seen between the catch-up growth of SGA and AGA infants in their 2 nd year of age; although the catch-up rate of SGA infants was detected to be lower than that of AGA infants during their follow-up, until their 2 nd year of age.…”
Section: Discussionmentioning
confidence: 99%
“…(25) 32 haftanın altındaki prematürelerde (36 aylık) boyca geriliği %12,8 olarak rapor etmişlerdir. Büyüme geriliğinde ventilatör tedavisi, ileri evre İKK, hidrosefali, anne sütü alamama ve nörogelişimsel gerilik risk faktörleri olarak bildirilmiştir.…”
Section: Discussionunclassified